ANALISIS WACANA KRITIS MODEL ROGER FOWLER TERHADAP BERITA ONLINE DETIK.COM - Nurhayati, Nurhayati; Ray, Sukma Adelina; Kusyani, Diah; Ahyunisa, Dian (Pedagogi: Jurnal Ilmiah Pendidikan, 2025)
This research aims to analyze Roger Fowler's critical discourse model on detik.com online news. The research method used is a qualitative method with descriptive techniques. The data collection method in this research is the documentation method. The object of the research is two news articles that discuss corruption cases with different impacts, namely the Harvey Moeis case with a state loss of Rp 300 trillion and a sentence of 6.5 years, and the corruption case of the Ruteng airport terminal project with a loss of Rp 8 billion and charges of 5 to 8 years. The results showed that the media used linguistic strategies such as classification vocabulary, view restrictions, and marginalization to shape public opinion. In the Harvey Moeis case, the much lighter sentence compared to the amount of state losses reflected the inequality in the justice system, which then led to strong criticism from the public. Meanwhile, in the case of the Ruteng airport terminal project, the media emphasized the severity of the sentence, even though the scale of the loss was much smaller than the Harvey Moeis case. This research confirms that language in the media not only functions as a communication tool, but also has a role in shaping public perceptions of legal justice.